The Dispute over the Attribution of a Ghazal to Saadi, Mahseti, and Rafi' Marvazi - Amin Yaghubi; Mehdi Dehgan (تاریخ ادبیات)
IntroductionMany of the diwans (poetic collections) of ancient poets have been lost for various reasons. This has led to reliance on tazkarehs (biographical works) and jongs (literary anthologies) for compiling the poetic works of the poets without preserved diwans. Although the existence of these tazkarehs and jongs is a great blessing, sometimes the authors' or scribes' errors result in attributing a poem to someone else. However, referring to tazkarehs and jongs is the only way to gather the works of poets without preserved diwans, albeit with caution. The oldest and perhaps the most authoritative tazkareh of Persian poetry is Lobab al-Albab; this tazkareh provides abundant and documented information about poets before the 6th century and serves as a source for other tazkarehs and historical books. Based on the editors' statements in Lobab al-Albab, this tazkareh was edited based on two manuscripts by Elliot and Sprenger, which Browne stated were from the 16th or 17th century AD, approximately the 10th or 11th century AH (See: Aufi, 1982: 7). And elsewhere, he states that: “In fact, none of the manuscript copies used as the basis possesses significant antiquity or scholarly precision” (ibid: 19). However, this lateness of the manuscripts of Lobab cannot be a reason for major alterations in the poems, and on this basis, it can be considered one of the most authentic sources for poems before the 6th century, as it was of interest to the authors of tazkarehs, and many later tazkarehs, literary works, and historical books have cited it. After Lobab, various tazkarehs and jongs such as Rawzat al-Nazir, Arafat al-Ashiqin, Atishkadeh, Aftab-e Alamtab, Ruz-e Rushan, Majales al-Nafais, and similar tazkarehs were compiled. Although the main benefit of these tazkarehs is the collecting poems and biographies of earlier poets, especially those without preserved diwans, they sometimes contain attribution errors. In such cases, the most logical approach is referring to the earliest of these tazkarehs and jongs and their consensus on a subject and presenting rational evidence to minimize errors. Literature ReviewThere are various articles and editions regarding Mahseti Ganjavi and the quatrains attributed to him. One of the oldest articles related to Mahseti is “Mahseti Nayshaburi” by Ali Akbar Qawim al-Dowleh, in which he mentions Mahseti Nayshaburi through a narration from Sultan Sanjar (Qawim al-Dowleh, 1960: 161-168). Among the most important articles about Mahseti is “Mahseti-shenasi” by Maryam Mosharraf, which discusses Mahseti's life and introduces two books about him (Mosharraf, 2005: 85-101). There is also an article titled “Stylistic Analysis of Mahseti Ganjavi's Quatrains” by Mohammad Reza Najjarian, which lists his stylistic characteristics (Najjarian, 2016: 241-268). There are more articles about Mahseti, but they are beyond the scope of this research. However, none of the aforementioned studies mention the attribution of the ghazal in question to Mahseti Ganjavi. Furthermore, this ghazal is not present in any of the editions of Mahseti's quatrains. Additionally, the authors of this research did not find any studies on the works and potential poems of Rafi' Marvazi. There has also been no research regarding the attribution of this ghazal to Saadi. MethodsThe method of data collection in the present research is library-based and note-taking. In this study, a descriptive-analytical approach is used to examine a ghazal attributed to three poets. Several manuscripts and printed copies have also been studied to reach the most accurate conclusion. DiscussionOne of the current problems regarding the poems of past poets is the wandering of some of these poems in different jongs and tazkarehs. A famous ghazal attributed to Saadi, and also included as a “mukhammas” (five-line poem based on another poem) on Saadi's ghazal in Helali Joghatayi's diwan, is recorded with Saadi's pen name. However, after examining Saadi's Kolliyat (complete works) and scrutinizing several manuscripts, we did not find this ghazal in Saadi's diwan. This ghazal, present in Helali's “tazmin” (incorporation), also has Saadi's pen name. It is attributed to Mahseti in the tazkareh Biyaz by Taj al-Din Ahmad Wazir and the jong Rawzat al-Nazir wa Nuzhat al-Khatir by Abdulaziz Kashi. A critical point that casts doubt on these attributions is the inclusion of this ghazal in Lobab al-Albab under the name of Rafi' Marvazi. Considering that Lobab precedes all of these works, the attribution of the ghazal to Mahseti and Saadi becomes questionable. Furthermore, in three instances in Jawame’ al-Hekayat, Tarikh-e Jahangushay-e Juvayni, and Makaram al-Akhlaq, a line or lines from this ghazal are mentioned; and given the historical periods of these books, its attribution to Saadi is impossible. Moreover, the attribution of the ghazal to Rafi' takes precedence over Mahseti, as the ghazal in question is attributed to Rafi' Marvazi in Lobab, which is earlier than the other manuscripts. ConclusionGiven that the ghazal in question is attributed to Rafi' Marvazi in Lobab al-Albab by Aufi, and since Rafi' Marvazi was a poet of the Seljughi era, while Saadi is later than him and even the author of Lobab, it can be said with certainty that this ghazal is not by Saadi. The inclusion of two lines from this poem without mentioning the author's name in Jawame’ al-Hekayat, Tarikh-e Jahangushay, and Makaram al-Akhlaq is Another reason to reject its attribution to Saadi. The attribution of this ghazal to Mahseti should also be doubted, as the oldest tazkareh closest to Mahseti's time has attributed it to Rafi' Marvazi. Additionally, this ghazal differs from Mahseti's poems in terms of stylistic and poetic form. Therefore, considering the refutation of its attribution to Saadi and the doubt in its attribution to Mahseti, it is logical and more accurate to trust Lobab and attribute it to Rafi' Marvazi.